2022
DOI: 10.1136/openhrt-2022-002084
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac postacute sequelae symptoms of SARS-CoV-2 in community-dwelling adults: cross-sectional study

Abstract: ObjectiveTo examine risk factors for cardiac-related postacute sequelae of SARS-CoV-2 infection (PASC) in community-dwelling adults after acute COVID-19 infection.MethodsWe performed a cross-sectional analysis among adults who tested positive for COVID-19. Outcomes were self-reported cardiac-related PASC. We conducted stepwise multivariable logistic regression to assess association between the risk factors (existing cardiovascular disease (CVD), pre-existing conditions, days since positive test, COVID-19 hospi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Indeed, in the article reviewed, the new-onset HT was identified using the relative ICD-10 codes. However, our findings are in accordance with those presented by Zhang et al [9] and Ogungbe et al [22], which demonstrated am increased risk for essential HT after COVID-19 infection.…”
Section: Discussionsupporting
confidence: 94%
“…Indeed, in the article reviewed, the new-onset HT was identified using the relative ICD-10 codes. However, our findings are in accordance with those presented by Zhang et al [9] and Ogungbe et al [22], which demonstrated am increased risk for essential HT after COVID-19 infection.…”
Section: Discussionsupporting
confidence: 94%
“…The included studies varied in their definition of “post-COVID-19 condition”: five studies referred to the NICE guidelines [ 47 , 50 , 55 , 57 , 58 ], four based their analyses on the WHO clinical case definition [ 44 , 53 , 56 ], two referred to a temporal definition of the Centers for Disease Control and Prevention (CDC), that cannot be found online any more [ 41 , 43 , 45 ] and eight studies did not use any standardized evidence-based definition to operationalize long-term health effects of COVID-19 [ 42 , 46 , 48 , 49 , 51 , 52 , 54 , 59 ]. Figure 2 shows observation periods of the included studies in relation to the acute COVID-19 infection.…”
Section: Resultsmentioning
confidence: 99%
“…Hirschtick et al also provided two analyses based on two different time measurements, which they labelled as “30+ day COVID-19” for symptoms persisting for 30 or more days and “60+ day COVID-19” for symptoms lasting for 30 or more or 60 or more days after acute SARS-CoV-2 infection [ 46 ]. Five studies measured symptoms earlier than 4 weeks after disease onset [ 41 , 48 , 49 , 51 , 54 ]. Fifteen included studies based their analyses on self-reported long-term health effects of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Other reported risk factors are poor pre-pandemic mental health, poor general health, and underlying asthma [ 13 ]. With respect to cardiovascular symptoms of PASC, patients with underlying cardiovascular disease (coronary artery disease, hypertension, atrial fibrillation), pre-existing diseases (asthma, diabetes, kidney disease, cancer), and prior hospitalization for COVID-19, have been associated with a higher risk [ 14 ]. The exact pathophysiology with respect to risk factors is yet to be understood fully and requires further research.…”
Section: Reviewmentioning
confidence: 99%